The Theoretical Evaluation of the Possibility of Theacrine Electrochemical Detection Over the Cubic Nanoparticles of CoSn(OH)6 - Романів, Людмила Вікторівна (Der Pharma Chemica, 2017)
The possibility of theacrine electrochemical determination, assisted by cubic nanoparticles of CoSn(OH)6 has been evaluated from the theoretical point of view. The correspondent mechanism has been suggested, and the correspondent model, developed and analyzed by means of linear stability theory and bifurcation analysis. It was verified that theacrine may be electrochemically detected in neutral or lightly alkaline media over CoSn(OH)6 . The analytical signal has to be clear and easily interpreted. The possibility of oscillatory and monotonic instabilities has also been verified.
Keywords: Food security, Theacrine, Cobalt-tin hydroxide, Electrochemical sensor, Stable steady-state